The new dimension of silver. Issue 30 (14th August 2015) - Yang, Li-Ming; Frauenheim, Thomas; Ganz, Eric
<x xml:space="preserve">Abstract</x> We predict a novel and highly stable 2D Ag monolayer featuring planar hexacoordinate silver.